ANTENATAL CORTICOSTEROIDS - BETWEEN BEING A USEFUL DRUG AND POSING A RISK FOR FETAL AND ADULT DEVELOPMENT - Babovic, Ivana; Dotlic, Jelena; Sparic, Radmila; Plesinac, Vera; Plesinac, Jovana; Bila, Jovan; Micic, Jelena; Jovandaric, Miljana; Karadzov Orlic, Natasa; Andjic, Mladen (Medical Research, 2023)
Abstract: Antenatal corticosteroid therapy (ACST) is very important in reducing the sequelae of prematurity, respiratory distress syndrome (RDS), intraventricular hemorrhage (IVH), and necrotizing enterocolitis (NEC). This therapy has short-term and long-term neonatal consequences that range from  reduced  neonatal body weight, brain growth, hypertension,  hypoglycemia and obesity to delayed neurological development. In addition to the undeniable importance this type of therapy has on  fetal maturation, it  may also impact the programming of the fetus’s future development and health during childhood and adulthood. ACST must be personalized, as a single course, and determined by the indications and  assessment of the expected time of delivery, so that the exposure time of the fetus to the effects of endogenous and exogenous steroids is shortened.
Keywords: antenatal corticosteroid therapy, programming, prematurity, fetus, neonate